Characteristics of Fibre-Reinforced Cement-Sand Blocks with Quarry Dust as Replacement for Sand - Jijo James; S. V. Sivapriya (The Scientific World Journal)
The present investigation delved into the mechanical performance of fibre-reinforced cement-sand blocks with quarry dust as a replacement for sand. The introduction of fibres and quarry dust in the matrix is an attempt to achieve higher performance with available cement content and reduce the utilization of natural sand to improve the sustainability of the product. The experimental programme attempted to study the influence of quarry dust on the density, compressive strength, water absorption, sorptivity, and efflorescence characteristics of the blocks. The parameters considered include quarry dust (QD) content (replacement of sand from 0% to 100% in increments of 20%), a constant fibre content of 0.5%, and a constant water-cement ratio of 0.5. An attempt was also made to compare the strength performance of the blocks with various code requirements as well as results from similar previous investigations. The replacement of sand with QD resulted in a reduction in the density of the blocks from 2365 kg/m3 to 2008 kg/m3. The results of the investigation revealed that 60% quarry dust replacement of natural sand developed the maximum strength of the blocks. After 28 days of curing, blocks with up to 60% QD replacement were able to produce strength more than 16 MPa. The water absorption increased only marginally from 5.52% to 5.83% for 60% QD replacement. Moreover, the blocks were able to meet the requirements of all the different types of blocks as stipulated by Bureau of Indian Standards including stabilized soil blocks, concrete solid blocks, concrete hollow blocks, lime-based blocks, and lime-flyash blocks of class up to 17.5.